Enhancing The Tenth Grade Students’ Active Participation And Reading Comprehension Achievement By Using Know, Want, Learned (KWL) Strategy - Robi Nurmiftah; Aan Erlyana Fardhani; Wiwiek Eko Bindarti (English Education Study Program, 2021)
This classroom action research was intended to enhance students’ active participation and reading comprehension achievement by using KWL strategy. The research participants of the study were 31 students of X IPA 2 at SMAN Tamanan, Bondowoso. The implementation of KWL strategy could enhance the X IPA2students’ active participation in teacher learning process of reading comprehension. The result of observation showed that the percentage of the students who were active before the action was 22.5%. After the action in Cycle1, the percentage of the students who were active increased to 75.5% while in Cycle2 was 87%.Moreover, the implementation of KWL strategy could enhance the X IPA 2students’ reading comprehension achievement. The result of reading comprehension test showed that the percentage of students who got score ≥73improved from 0% in the previous reading score to 76% in Cycle1 and 88% in Cycle2. Both the result of observation and reading achievement test had achieved the target minimum criteria of the success of classroom action research that was 75%.